CARE Guidelines for Case Reports: Explanation and Elaboration Document. Translation into Russian - David S. Riley; Melissa S. Barber; Gunver S. Kienle; Jeffrey K. Aronson; Tido von Schoen-Angerer; Peter Tugwell; Helmut Kiene; Mark Helfand; Douglas G. Altman; Harold Sox; Paul G. Werthmann; David Moher; et al. (Вопросы современной педиатрии, 2023)
Background. Well-written and transparent case reports (1) reveal early signals of potential benefits, harms, and information on the use of resources; (2) provide information for clinical research and clinical practice guidelines, and (3) inform medical education. High-quality case reports are more likely when authors follow reporting guidelines. During 2011–2012, a group of clinicians, researchers, and journal editors developed recommendations for the accurate reporting of information in case reports that resulted in the CARE (CAse REport) Statement and Checklist. They were presented at the 2013 International Congress on Peer Review and Biomedical Publication, have been endorsed by multiple medical journals, and translated into nine languages.Objectives. This explanation and elaboration document has the objective to increase the use and dissemination of the CARE Checklist in writing and publishing case reports.Article design and setting. Each item from the CARE Checklist is explained and accompanied by published examples. The explanations and examples in this document are designed to support the writing of high-quality case reports by authors and their critical appraisal by editors, peer reviewers, and readers.Results and conclusion. This article and the 2013 CARE Statement and Checklist, available from the CARE website [www.care-statement.org] and the EQUATOR Network [www.equator-network.org], are resources for improving the completeness and transparency of case reports.Source. This article is a translation of the original paper «CARE guidelines for case reports: explanation and elaboration document» in the Journal of Clinical Epidemiology (doi: 10.1016/j.jclinepi.2017.04.026), prepared under the permission of the copyright holder (Elsevier Inc.), with supervision from the Scientific Editor by Professor E.G. Starostina, MD, PhD (translator) (Moscow, Russia). Present translation was first published in Digital Diagnostics. doi: 10.17816/DD105291. It is published with minor changes related to the literary editing of the translation itself. Keywords: case report; case study; EQUATOR network; health research reporting guidelines; CARE guideline; timelines; N-of-1 For citation: Riley David S., Barber Melissa S., Kienle Gunver S., Aronson Jeffrey K., von Schoen-Angerer Tido, Tugwell Peter, Kiene Helmut, Helfand Mark, Altman Douglas G., Sox Harold, Werthmann Paul G., Moher David, Rison Richard A., Shamseer Larissa, Koch Christian A., Sun Gordon H., Hanaway Patrick, Sudak Nancy L., Kaszkin-Bettag Marietta, Carpenter James E., Gagnier Joel J. CARE Guidelines for Case Reports: Explanation and Elaboration Document. Translation into Russian. Voprosy sovremennoi pediatrii — Current Pediatrics. 2023;22(2):88–108. (In Russ). doi: https://doi.org/10.15690/vsp.v22i2.2540